A Principle of Incarnation in Derrida’s (Theologische?) Jugendschriften: Towards a Confessional Theology - Smith, James K. A. (Modern theology, 2002)
In pursuing the question of incarnation, it must be noted from the beginning that what is at stake is Platonism. More specifically, my concern will be the relationship of Christian theology to Platonism. In this paper, I contest contemporary readings which suggest that Socrates offers an "incarnational" paradigm and construe Derrida as a "Platonist" more traditionally understood. Instead, I will argue that latent in Derrida’s earlier accounts of language, particularly in Speech and Phenomena, one finds an incarnational account of language which is precisely the basis for his critique of Platonic metaphysics.